Neuroblastoma-targeted Anticancer Drug Delivery - Safiye Aktaş; Özde Elif Gökbayrak; Aylin Erol; Hatice Nur Olgun (Galenos Publishing House, 2021)
Neuroblastoma (NB) is the most common solid tumor in pediatric cases. NB accounts for about 8% of malignancies in patients younger than 15 years, and since 50% of newly diagnosed cases metastasize to regional lymph nodes, bone marrow, bone, liver, and skin, the disease is usually diagnosed in its late stages. Overexpression of N-MYC, which is characterized by poor prognosis in NB, changes the progression of the disease and the course of the treatment. Targeting these pathways may be a treatment option in NB, since the mTOR and AURKA pathways interact with N-MYC and directly cause protein stabilization. The widespread use of conventional chemotherapeutics has some limitations associated with their common side effects and the bioavailability of the drugs. New therapeutic approaches have focused on nanoparticle (NP) -based therapies, and chemoimmunoagents in the form of many NPs are being tried in NB. Here, we review new therapeutic approaches that would help to treat NB.